A multi-objective co-evolutionary algorithm for energy-efficient scheduling on a green data center. (November 2016) - Lei, Hongtao; Wang, Rui; Zhang, Tao; Liu, Yajie; Zha, Yabing
Abstract: Nowadays, the environment protection and the energy crisis prompt more computing centers and data centers to use the green renewable energy in their power supply. To improve the efficiency of the renewable energy utilization and the task implementation, the computational tasks of data center should match the renewable energy supply. This paper considers a multi-objective energy-efficient task scheduling problem on a green data center partially powered by the renewable energy, where the computing nodes of the data center are DVFS-enabled. An enhanced multi-objective co-evolutionary algorithm, called OL-PICEA-g, is proposed for solving the problem, where the PICEA-g algorithm with the generalized opposition based learning is applied to search the suitable computing node, supply voltage and clock frequency for the task computation, and the smart time scheduling strategy is employed to determine the start and finish time of the task on the chosen node. In the experiments, the proposed OL-PICEA-g algorithm is compared with the PICEA-g algorithm, the smart time scheduling strategy is compared with two other scheduling strategies, i.e., Green-Oriented Scheduling Strategy and Time-Oriented Scheduling Strategy, different parameters are also tested on the randomly generated instances. Experimental results confirm the superiority and effectiveness of the proposed algorithm. Abstract : Highlights: We consider multi-objective energy efficient scheduling on a green data center. The task model, energy model and scheduling model are defined for the problem. An enhanced PICEA-g algorithm is proposed for solving the problem. The proposed algorithm is compared and tested on the generated instances.